Advances and challenges in machine learning-based identification of organic pollutant sources in heterogeneous aquifers - Yue Zhang; Mingxu Cao; Zhenxue Dai; Hao Wang; Sida Jia; Lulu Xu; Xiaoying Zhang; Mohamad Reza Soltanian; Javier Samper Calvete; Huichao Yin; Kenneth C. Carroll (Journal of Environmental Chemical Engineering, 2026)

An open, reproducible benchmark of daily CO2 forecasting models with applications to GHG monitoring - Pablo Catret-Ruber; David Garcia-Rodriguez; Domingo J. Iglesias Fuente; Ernesto López-Baeza; J. Javier Samper-Zapater; Juan José Martínez Durá (Environmental Modelling & Software, 2026)

Bio-mediated enhancement of supergene copper mineralization: Evidence from Cu isotope geochemistry - J. Javier Rey-Samper; Ryan Mathur; Fernando Tornos (Geochimica et Cosmochimica Acta, 2025)

Reactive transport model of the long-term geochemical evolution in a HLW repository in granite at the disposal cell scale: Variants, sensitivities, and model simplifications - Javier Samper; Alba Mon; Luis Montenegro (Applied Geochemistry, 2024)

Life-cycle assessment of hydrogen systems: A systematic review and meta-regression analysis - Gonzalo Puig-Samper; Eleonora Bargiacchi; Diego Iribarren; Javier Dufour (Journal of Cleaner Production, 2024)

2D model of groundwater flow and total dissolved HCH transport through the Gállego alluvial aquifer downstream the Sardas landfill (Huesca, Spain) - Brais Sobral; Javier Samper; Luis Montenegro; Alba Mon; Joaquín Guadaño; Jorge Gómez; Javier San Román; Felipe Delgado; Jesús Fernández (Journal of Contaminant Hydrology, 2024)

Identification of solute transport parameters in fractured granites with heterogeneous apertures - Mingxu Cao; Zhenxue Dai; Sida Jia; Javier Samper; Hui Ling; Zhengyang Du; Chuanjun Zhan; Zhijie Yang; Hung Vo Thanh; Mohamad Reza Soltanian (Journal of Hydrology, 2024)

Impact of reactive mineral facies distributions on radionuclide sorption properties in multiscale heterogeneous granite rocks - Wei Chen; Zhenxue Dai; Javier Samper; Hui Ling; Chuanjun Zhan; Funing Ma; Zhijie Yang; Xiaoying Zhang; Mohamad Reza Soltanian (Hydrogeology Journal, 2023)

A non-isothermal reactive transport model of the long-term geochemical evolution at the disposal cell scale in a HLW repository in granite - Luis Montenegro; Javier Samper; Alba Mon; Laurent De Windt; Aurora-Core Samper; Enrique García (Applied Clay Science, 2023)

Reactive transport models of the geochemical interactions at the iron/bentonite interface in laboratory corrosion tests - Alba Mon; Javier Samper; Luis Montenegro; María Jesús Turrero; Elena Torres; Jaime Cuevas; Raúl Fernández; Laurent De Windt (Applied Clay Science, 2023)

Hydrogeology and groundwater management in a coastal granitic area with steep slopes in Galicia (Spain) - Acacia Naves; Javier Samper; Bruno Pisani; Alba Mon; Jorge Dafonte; Luis Montenegro; Aitor García-Tomillo (Hydrogeology Journal, 2021)
Groundwater availability, management and protection are great challenges for the sustainability of groundwater resources in the scattered rural areas of the Atlantic regions of Europe where groundwater is the only option for water supply. This report presents a hydrogeological study of the coastal granitic area of Oia in northwestern Spain, which has unique geomorphological and hydrogeological features with steep slopes favoring the erosion of the weathered granite. The hydrogeological conceptual model of the study area includes: (1) the regolith layer, which is present only in the flat summit of the mountains; (2) the slope debris and the colluvial deposits, which are present in the intermediate and lowest parts of the hillside; (3) the marine terrace; and (4) the underlying fractured granite. Groundwater recharge from rainfall infiltration varies spatially due to variations in terrain slope, geology and land use. The mean annual recharge estimated with a hydrological water balance model ranges from 75 mm in the steepest zone to 135 mm in the lowest flat areas. Groundwater flows mostly through the regolith and the detrital formations, which have the largest hydraulic conductivities. Groundwater discharges in seepage areas, springs, along the main creeks and into the sea. The conceptual hydrogeological model has been implemented in a groundwater flow model, which later has been used to select the best pumping scenario. Model results show that the future water needs for domestic and tourist water supply can be safely provided with eight pumping wells with a maximum pumping rate of 700 m 3 /day.

Modeling cesium migration through Opalinus clay: a benchmark for single- and multi-species sorption-diffusion models - Jesús F. Águila; Vanessa Montoya; Javier Samper; Luis Montenegro; Georg Kosakowski; Philipp Krejci; Wilfried Pfingsten (Computational Geosciences, 2021)
Sophisticated modeling of the migration of sorbing radionuclides in compacted claystones is needed for supporting the safety analysis of deep geological repositories for radioactive waste, which requires robust modeling tools/codes. Here, a benchmark related to a long term laboratory scale diffusion experiment of cesium, a moderately sorbing radionuclide, through Opalinus clay is presented. The benchmark was performed with the following codes: CORE 2D V5, Flotran, COMSOL Multiphysics, OpenGeoSys-GEM, MCOTAC and PHREEQC v.3. The migration setup was solved with two different conceptual models, i) a single-species model by using a look-up table for a cesium sorption isotherm and ii) a multi-species diffusion model including a complex mechanistic cesium sorption model. The calculations were performed for three different cesium boundary concentrations (10 −3 , 10 −5 , 10 −7 mol / L) to investigate the models/codes capabilities taking into account the nonlinear sorption behavior of cesium. Generally, good agreement for both single- and multi-species benchmark concepts could be achieved, however, some discrepancies have been identified, especially near the boundaries, where code specific spatial (and time) discretization had to be improved to achieve better agreement at the expense of longer computation times. In addition, the benchmark exercise yielded useful information on code performance, setup options, input and output data management, and post processing options. Finally, the comparison of single-species and multi-species model concepts showed that the single-species approach yielded generally earlier breakthrough, because this approach accounts neither for cation exchange of Cs + with K + and Na + , nor K + and Na + diffusion in the pore water.

Parametric and numerical analysis of the estimation of groundwater recharge from water-table fluctuations in heterogeneous unconfined aquifers - Jesús F. Águila; Javier Samper; Bruno Pisani (Hydrogeology Journal, 2019)

Climate change impact on groundwater resources of a hard rock mountain region (Serra da Estrela, Central Portugal) - Bruno Pisani; Javier Samper; Jorge Espinha Marques (Sustainable Water Resources Management, 2019)

Dual-continuum multicomponent reactive transport with nth-order solute transfer terms for structured porous media - Liange Zheng; Javier Samper (Computational Geosciences, 2015)

Conceptualizing a mountain hydrogeologic system by using an integrated groundwater assessment (Serra da Estrela, Central Portugal): a review - Jorge Espinha Marques; José M. Marques; Helder I. Chaminé; Paula M. Carreira; Paulo E. Fonseca; Fernando A. Monteiro Santos; Rui Moura; Javier Samper; Bruno Pisani; José Teixeira; José Martins Carvalho; Fernando Rocha; et al. (Geosciences Journal, 2013)

Inverse Estimation of the Effective Diffusion of the Filter in the In Situ Diffusion and Retention (DR) Experiment - Shuping Yi; Javier Samper; Acacia Naves; Josep M. Soler (Transport in Porous Media, 2012)

Numerical evaluation of multicomponent cation exchange reactive transport in physically and geochemically heterogeneous porous media - Changbing Yang; Javier Samper (Computational Geosciences, 2009)

A sequential partly iterative approach for multicomponent reactive transport with CORE2D - Javier Samper; Tianfu Xu; Changbing Yang (Computational Geosciences, 2009)

A Subgrid-Scale Stabilized Finite Element Method for Multicomponent Reactive Transport through Porous Media - Changbing Yang; Javier Samper (Transport in Porous Media, 2009)

A semi-analytical solution for linearized multicomponent cation exchange reactive transport in groundwater - Javier Samper-Calvete; Changbing Yang (Transport in Porous Media, 2007)